THE ADVANTAGES AND CHALLENGES OF INTERNET FOR HIGHER EDUCATION - Habiburrahim Habiburrahim (Jurnal Ilmiah Didaktika, 2012)
In the new millennium, the internet plays an important role in improving the quality of education. Internet has become one of the means of communication, discussion, and even exploration of varieties of information from and between different worlds. In the world of education in the West, for example, the internet is used as a means of transforming education, especially by those who are dealing with the limitations of time and geographical location. The internet allows students and professors to communicate and coordinate with each other on the progress of the research they are doing. The internet, through its search engines, also has made it easier for education person to find diverse scientific literatures. Thousands of books, studies, research articles, reports and scientific papers are now available online. However, behind the ease and benefit of the search engines, educational practitioners scrutinize the implications of the use of the internet to the world of education. The internet is often misused or used as a medium to perform a variety of crimes. Stealing other people's private information and money, provocation and scorn as well as accessing pornographic sites are a a few number of examples that are always connected to the use of internet. The issue of infringement on intellectual property rights and other plagiarism is also very often associated with the misuse of the internet today. But this particular article describes the benefits of the internet through search engines, potential challenges, and benefits for higher education.